The influence of job stress and motivation to work performance - Subagyo Adam, Fransiska Dyah Ayu Puspitasari, (Opción, 2019)
The aim of the study is to investigate the influence of job stress and motivation to work performance at Satuan Polisi Pamong Praja Kabupaten Gresik via quantitative methods by using three different questionnaires with Likert scale. This survey has shown that as partial by using t-test and 5% significant, job stress and job motivation affect to job performance significantly, also by using F-test and 5% significant, known that as simultaneously, job stress and job motivation has a significant effect to job performance. In conclusion, job performance can be enriched when job stress condition is less and job motivation is high.